(untitled) (Journal of actual problems of jurisprudence, 2021)
Violations against children incorporate physical and enthusiastic mishandle; disregard; and misuse. Guardians, relatives, gatekeepers, frequently commit violations including children and others endowed with their care and direction. School authorities, specialists, police officers, and other such specialists are required to report any signs of mishandle or abuse of a child. The article looks at the Common characteristics of violations against children and the state of wrongdoing against children within the nation. In later a long time, the issue of savagery against children has ended up increasingly pressing not as it were in Kazakhstan, but all over the world. Violation against the life, wellbeing, sexual astuteness and sexual freedom of minors could be a ponder, illicit act beneath the criminal code of the Republic of Kazakhstan that hurts the ordinary advancement of the more youthful era. The security of the rights, flexibilities and genuine interface of minors, guaranteeing their legitimate ethical and mental improvement, and securing them from wrongdoing are the perpetual and most imperative bearings of the state’s criminal policy. Minors, due to the idiosyncrasies of their physical and mental improvement, are more vulnerable to different negative impacts than other categories of individuals, which can gotten to be the premise for the advancement of their individual deviation. Thousands of children are casualties of wrongdoing each year. Keywords: crime, minor, victim, victim of crimes, victimology, crimes against minors, statistics, juvenile victimology. References: [1] Aleksejchenko N. E. Organizacija raboty po profilaktike, vyjavleniju prestuplenij seksual’nogo haraktera, sovershennyh v otnoshenii detej i okazaniju pomoshhi zhertvam, poterpevshim nasilie // Materialy regional’noj konferencii. Zashhita prav detej ot seksual’nyh prestuplenij i posjagatel’stv [Organization of work on prevention, detection of sexual crimes committed against children and assistance to victims, victims of violence / / Materials of the regional conference. Protection of children’s rights from sexual crimes and assaults]. – Kemerovo, – 2013. – S. 60. – 44-52 s. https://deti.kemobl.ru/upload/iblock/26a/26a3369bcd8e075ec804e54 02525b682.pdf [2] V Kazakhstane uzhestochili nakazanie za prestuplenija protiv nesovershennoletnih [Kazakhstan has toughened the punishment for crimes against minors]. https://24.kg/biznes_info/139717_vkazahstane_ujestochili_nakazanie_zaprestupleniya_protiv_nesovershennoletnih/ [3] Vsemirnaja organizacija zdravoohranenija. Zhestokoe obrashhenie s det’mi. INSPIRE: Sem’ strategij po likvidacii nasilija v otnoshenii detej [World Health Organization. Child abuse. INSPIRE: Seven strategies to eliminate violence against children]. – 2016. – 14 s. https://www.who.int/ru/news-room/fact-sheets/detail/child-maltreatment [4] Vsemirnaja organizacija zdravoohranenija. Nasilie i ego vlijanie na zdorov’e. Doklad o situacii v mire. [ World Health Organization. Violence and its impact on health. Report on the situation in the world]. – 2002. – 346 s. [5] Vsemirnaja Organizacija Zdravoohranenija. Zhestokoe obrashhenie s det’mi. Informacionnyj bjulleten’ N 150.[ World Health Organization. Child abuse. Information bulletin N 150.] – 2010. – 14 s. [6] Widom C.S. Post-traumatic stress disorder in abused and neglected children grown up // American Journal of Psychiatry. [Posttraumatic stress disorder in abused and neglected children grown up // American Journal of Psychiatry]. – 1999. – Vol. 156, № 8. – P. 1223–1229. [7] Deklaracija prav rebenka. Prinjata rezoljuciej 1386 (HIV) General’noj Assamblei OON ot 20 nojabrja 1959 goda. [Declaration of the Rights of the Child. Adopted by the UN General Assembly resolution 1386 (XIV) of November 20, 1959]. // https://www. un.org/ru/documents/decl_conv/declarations/childdec.shtml [8] Ignatenko V.I. Osnovy preduprezhdenija antiobshhestvennogo obraza zhizni i recidiva prestuplenij nesovershennoletnih. [Fundamentals of prevention of antisocial lifestyle and recidivism of juvenile delinquency]. – Rjazan’: Form, – 1996. – 190 s. [9] Specializirovannyj mezhrajonnyj sud po delam nesovershennoletnih goroda Almaty (arhiv Delo № 7530-17-00-1/42) [Specialized Inter-district Juvenile Court of Almaty (archive Case No. 7530-17-00-1/42)]// https://almaty.sud.kz/rus/sub/juvenal [10] Konstitucija Respubliki Kazahstan (prinjata na respublikanskom referendume 30 avgusta 1995 goda) [The Constitution of the Republic of Kazakhstan (adopted at the republican referendum on August 30, 1995)] // http://online.zakon.kz/Document/?doc_ id=1005029#pos=1221; -246 [11] Levitan, R. D., N. A. Rector, Sheldon, T., & Goering, P. (2003). “Childhood adversities associated with major depression and/ or anxiety disorders in a community sample of Ontario: Issues of co-morbidity and specificity, “ Depression & Anxiety. – Vol. – 17. – P. -34-42. [12] Malkova V.D. Kriminologija [Criminology]. – M.: Justicinform.- 2006. – 245 s. [13] Mamyrhanova M. 550 prestuplenij protiv polovoj neprikosnovennosti detej soversheno s nachala goda v Kazahstane [550 crimes against the sexual integrity of children have been committed since the beginning of the year in Kazakhstan] // https://liter.kz/ mvd-s-nachala-goda-soversheno-550-prestuplenij-protiv-polovoj-neprikosnovennosti-nesovershennoletnih/ [14] Novyj global’nyj otchet: polovina detej v mire stradajut ot fizicheskogo, seksual’nogo ili psihologicheskogo nasilija. 23 ijunja 2020 g. [New global report: Half of the world’s children suffer from physical, sexual or psychological abuse] // https://www.unicef. org/kazakhstan [15] Poslanie Glavy gosudarstva Kasym-Zhomarta Tokaeva narodu Kazahstana 2 sentjabrja 2019 g. [Message of the Head of State Kassym-Jomart Tokayev to the people of Kazakhstan on September 2, 2019] //https://www.akorda.kz/ru/addresses/addresses_of_ president/poslanie-glavy-gosudarstva-kasym-zhomarta-tokaeva-narodu-kazahstana [16] Prestupnost’ v otnoshenii detej [Crime against children] // https://riss.ru/article/7494/ [17] Raisova Z. Kazakhstan: Tol’ko po 39 % ugolovnyh del po nasiliju v otnoshenii nesovershennoletnih vynosjat sudebnye prigovory [Under the new law, there will be no compromises between victims and rapists] // https://cabar.asia/ru/kazahstan-tolko-po39-ugolovnyh-del-po-nasiliyu-v-otnoshenii-nesovershennoletnih-vynosyat-sudebnye-prigovory/ [18] Raisova Z. Po novomu zakonu nikakih kompromissov u zhertv s nasil’nikami ne budet [Under the new law, there will be no compromises between victims and rapists] // https://liter.kz/22204-2/ [19] Roosa, M.W.; Reinholtz, C.; Angelini, P.J. The relation of child sexual abuse and depression in young women: comparisons across four ethnic groups // Journal of Abnormal Child Psychology journal. – 1999. – Vol. 27, no. 1. – P. 65–76. – PMID 10197407. [20] Sabekov S. Bolee 400 prestuplenij, svjazannyh s nasiliem nad det’mi, sovershili v RK s nachala goda [More than 400 crimes related to violence against children have been committed in Kazakhstan since the beginning of the year] // https://www.inform.kz/ru/ bolee-400-prestupleniy-svyazannyh-s-nasiliem-nad-det-mi-sovershili-v-rk-s-nachala-goda_a3659626 [21] Dannye o kolichestve lic, osuzhdjonnyh za sovershenie ugolovnyh pravonarushenij protiv polovoj neprikosnovennosti nesovershennoletnih [Data on the number of persons convicted of committing criminal offenses against the sexual integrity of minors] // http://infopublic.pravstat.kz/ped/ [22] Stat. dannye Upravlenija komiteta pravovoj statistike i special’nym uchetam general’noj prokuratury Respubliki Kazakhstan [Statistical data of the Department of the Committee for Legal Statistics and Special Accounts of the Prosecutor General’s Office of the Republic of Kazakhstan] // http://pravstat.prokuror.gov.kz/rus/o-kpsisu/deyatelnost-komiteta/analiticheskaya-informaciya [23] Fedorov A. I. Rabota po zashhite prav detej ot seksual’nyh prestuplenij i posjagatel’stv v sisteme obrazovatel’nyh uchrezhdenij Kemerovskoj oblasti // Materialy regional’noj konferencii. Zashhita prav detej ot seksual’nyh prestuplenij i posjagatel’stv [Work on the protection of children’s rights from sexual crimes and encroachments in the system of educational institutions of the Kemerovo region // Materials of the regional conference. Protection of children’s rights from sexual crimes and assaults]. – Kemerovo, – 2013. –S. 60. – 37-43 s. https://deti.kemobl.ru/upload/iblock/26a/26a3369bcd8e075ec804e5402525b682.pdf